The effect of Ge precursor on the heteroepitaxy of Ge1-xSnx epilayers on a Si (001) substrate - Jahandar, Pedram; Weisshaupt, David; Colston, Gerard; Allred, Phil; Schulze, Jörg; Myronov, Maksym (Semiconductor Science and Technology, 2018)
The heteroepitaxial growth of Ge1-xSnx on a Si (001) substrate, via a relaxed Ge buffer, has been studied using two commonly available commercial Ge precursors, Germane (GeH4) and Digermane (Ge2H6), by means of chemical vapour deposition at reduced pressures (RP-CVD). Both precursors demonstrate growth of strained and relaxed Ge1-xSnx epilayers, however Sn incorporation is significantly higher when using the more reactive Ge2H6 precursor. As Ge2H6 is significantly more expensive, difficult to handle or store than GeH4, developing high Sn content epilayers using the latter precursor is of great interest. This study demonstrates the key differences between the two precursors and offers routes to process optimisation which will enable high Sn content alloys at relatively low cost.
CRIS-Team Scopus Importer:2021-06-29
Keywords: CVD chemical vapour deposition; Ge; GeH; GeSn; Indirect-to-direct bandgap; Semiconductor; SiGeSn